Development and Performance Evaluation of Arduino-Based Environmental Monitoring System Integrating BME280 Sensor and BN-220 GPS - Asri Ramadhani, Siti Bulan; Kuncoro, Endo Argo; Noverdita, Noverdita (Fakultas Teknologi Industri Pertanian, 2025)
The development of BME280 sensor and BN-220 GPS module based on Arduino Uno is a device that can measure temperature, humidity, air pressure and location coordinates in real-time. This research aims to compare the performance of the device with temperature, humidity, and air pressure sensors, as well as the Arduino Uno-based GPS module with the performance of existing measuring instruments at BMKG, Climatology Station. This research was conducted from September to December 2024 at the Sub-Laboratory of Agricultural Energy, Department of Agricultural Technology, Faculty of Agriculture, Sriwijaya University and BMKG, Class I Climatology Station, South Sumatra. The research method used, namely quantitative descriptive method which includes the development of hardware, software, testing, and measurement data displayed in the form of tables and graphs. The research was conducted by taking data per 1 hour starting from 08.00 to 16.00 WIB, the data obtained was compared with data from BMKG. This tool combines to measure environmental condition parameters, namely temperature, humidity, and air pressure, as well as location coordinates that can be used portable because it does not need to use the internet network to be able to display the measured parameters. The results obtained will appear on the LCD and the measurement data is stored directly on the SD card. This tool is able to provide real-time data and generate measurement data for each parameter simultaneously, so that farmers or users in remote areas can know the environmental conditions directly and take appropriate action. The comparison results show that the temperature parameter gets an average percentage difference of 4.01%, humidity is 11.2%, air pressure is 0.03%, and location coordinates have an average difference value of 2.9m. This tool is able to provide measurement data that is consistent and relatively the same as the data generated by BMKG.